On analysis of phthalocyanine network through statistical method - Hadeel AlQadi; Muhammad Farhan Hanif; Mazhar Hussain; Muhammad Kamran Siddiqui; Faryal Chaudhry; Mohamed Abubakar Fiidow (Scientific Reports)
Abstract Phthalocyanine derivative nanostructures are highly organized organometallic structures that exhibit two-dimensional polymeric phthalocyanine frameworks. We analyze phthalocyanine using the Zagreb-type indices, which offer important insights into the topological characteristics of the molecular structure. Furthermore, we use Pearson correlation analysis to examine the degree of relationship between various structural features and qualities. The significance of $$2D-TMPC$$ in materials research and the value of computational techniques in elucidating the chemical’s properties and possible uses as demonstrated by this multidimensional examination of the material. We use a Pearson correlation heat map to show the relation between indices and entropy.